Engineering wonders of the world. Volume I - Williams, Archibald, 1871-1934 (Thomas Nelson, 1891)
As the title implies, the whole world is covered by these volumes, with each entry selected on its own merits. English and continental railways, for instance, receive little notice, being overshadowed by the systems of America, Asia and Africa. For mountain tunnels we go to the Alps; for canals to Panama, Suez and the United States; a cableway in the Andes, and so on.